Pengaruh Motivasi, Persepsi Dan Sikap Konsumen Terhadap Keputusan Berbelanja Di Pasar Tradisional (Studi pada Konsumen Pasar Tradisional Dinoyo Kota Malang) - Sri Rezeki; Abdul Kodir Djaelani; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this research is to find out and analyze the results of the influence of motivation, perceptions and attitudes of consumers on shopping decisions in traditional markets. The method used in this research is quantitative. The population in this study were consumers of the Dinoyo traditional market in Malang. The sample in this study were 85 respondents. The sampling technique is simple random sampling. Data analysis using multiple linear regression. The results showed that the variables of motivation, perception and consumer attitudes had a positive and significant effect on shopping decisions simultaneously. Variable motivation has a partial effect on shopping decisions, perceptions have a partial positive and significant effect on shopping decisions, and consumer attitudes have a partial positive and significant effect on shopping decisions in traditional markets for consumers in Dinoyo traditional market, Malang city. Keywords: Motivation, Perception, Consumer Attitudes and Shopping Decisions